Congenital anonychia with brachydactyly with novel, unilateral congenital hypoglossal nerve palsy and staghorn renal calculus - Anita Marak; Ellis Khawbung; Shakeel A Jabbar; B Shakthi (Wolters Kluwer Medknow Publications, 2022)
Congenital anonychia is a relatively rare abnormality of nail development affecting all or some of the finger and toe nails, characterized by either complete absence of nails or hypoplasia of nails. We report a rare case of congenital anonychia with brachydactyly with unique congenital abnormalities of heart-shaped tongue, congenital hypoglossal nerve palsy, and staghorn calculus. To our knowledge, these associations have never been described before and do not fall under any known syndromic entity.